Bibliotherapy as an interdisciplinary therapeutic resource - Losada, Analia Veronica (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2020)
Bibliotherapy has been widely studied by various authors. As a therapeutic resource based on reading books, it has an interdisciplinary approach between psychology and library science. To broaden the subject, an interview with Antonio Martín Román, who has a degree in Library and Information Science and a Doctor in Social Psychology, which addresses the background of Bibliotherapy, the relationship with the meaning of life and with existential frustration or noogenic neurosis, and this researcher's theory about the benefits of applying this therapeutic resource in vulnerable populations.